PENGEMBANGAN INDUSTRI NON-CORPORATE PARTISIPATIF INTEGRATIF PADA INDUSTRI MINYAK ATSIRI KENANGA - Salviana DS, Vina (Jurnal Teknik Industri, 2012)
This research is considered as 'action research' which was tried to analyze the problems of aetheric oil industry made of Cananga flower. Research was held in Blitar Regency, East Java, as one of center aetheric oil production in Indonesia,which has potential to increase its production up to international scale. Based on this perspective, it was important to build such community empowerment based on integrative-participative model through business industry groups with basic characteristic non-corporate as suitable alternative for the development of Cananga farmer community. The results of this research were enhance distilation process, dealing with the waste from the distilation process, expanding the business unit of aroma therapy as the main product and also improving business mentality through some training activity for business motivation building.